PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS V SDN 14 PAUH KOTA PADANG - Kurniasari, Ningrum Adji; Anita, Yesi; Muhammadi, Muhammadi; Sukma, Elfia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this research is to describe the improvement in Pancasila Education learning outcomes using the Problem Based Learning (PBL) model in class V of SDN 14 Pauh, Padang City. This research applies a type of Classroom Action Research (PTK) using qualitative and quantitative approaches. The subjects in this research were teachers (researchers) and 19 students consisting of 8 men and 11 women. The results of this research show an increase in: a) teaching modules in cycle I with an average of 85.41% (Good) and cycle II 95,83% (very good), b) implementation in the teacher aspect of cycle I with an average of 82.14% (Good) and cycle II 96.42% (Very Good), while implementation in the student aspect of cycle I averaged 82.14% (Good) and cycle II 96.42% (Very Good), c) assessment of students in improving results learning in cycle I obtained 74.94% and cycle II with an average of 85.76%. Based on these results, it can be concluded that the Problem Based Learning (PBL) model can improve Pancasila Education learning outcomes in class V.